The Criminal Law & Muamalah Studies on the Affiliator Role of Binary Option Transaction - Any Ismayawati; Inna Fauziatal (Jurnal Akta, 2022)
The development of the digital world today has not been fully followed by the development of human capabilities in the digital field. This is what gives rise to various problems, especially in facing the trend of digital transactions, such as Binary Option. The most obvious impact in digital transactions is the emergence of affiliates who take huge profits on the losses of their transaction partners. Regarding to above statement, this study aims to explore the role of trading affiliater in digital transactions, the performative function of criminal law, and the perspective of sharia contracts in muamalah about Binary Option. The method of this research is normative research using a statutory approach in criminal law and sharia contracts in muamalah. The results showed that the role of affiliates in Binary Option is to influence business people to enter the circle of online type transactions, by promoting that Binary Option are fast, easy and very profitable transactions. In the perspective of criminal law shows that those committed by affiliates in Binary Option are included in the criminal act of fraud. Likewise in muamalah, digital transactions such as Binary Option are classified as prohibited transaction because it contains elements of Gharar and it is not called selling in Islam.